Women and Youth in Agriculture in the Southern African Development Community (SADC) Region - Kasase, Chitundu; Rasoanindrainy, Andrianjafy; Kakuwa, Bridget; Baitsi Podisi, Baitsi; Magagula, Futhi; Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The recent symposium was a truly empowering and enriching experience for all participants, showcasing a remarkable diversity of profiles, topics, talents, and commitments within the agricultural sector in the SADC region. This symposium brought together a wide range of stakeholders, including young farmers, experienced entrepreneurs, researchers, and government representatives, creating a dynamic platform for interaction and collaboration. Participants unanimously agreed on the significant benefits of the event, highlighting the valuable insights, techniques, and inspiration gained, which they plan to apply to their businesses or projects. The stories and experiences shared deeply inspired many attendees, while others acquired detailed knowledge about new practices and innovative approaches. Described as "a success" by all, the workshop stood out for its diversity, quality, intensity, and depth of discussions and presentations. Key topics included indigenous crops and knowledge systems, dairy farming, the cashew business, beekeeping, aquaculture, mushroom farming, organic agriculture, and the importance of mentorship in farming. Additionally, the event underscored the crucial role of women in agriculture and the potential of youth in driving sector innovation. The following report presents a summary of the workshop's key discussions, insights, and recommendations, aimed at fostering a vibrant community of agricultural innovators and entrepreneurs across the SADC region